Bahaya Judi Online : Dampak Sosial, Ekonomi, Dan Kesehatan - Angga Nurdiansyah; Ageng Saepudin Kanda (Pusat Riset dan Inovasi Nasional, 2024)
The increasing ease of internet access has led to its misuse in the form of online gambling. Initially, online games served as the entry point, but curiosity and interest have driven teenagers to participate in online gambling. Kartono (2014) defines gambling as the intentional act of risking something valuable with awareness of the associated risks and specific expectations for uncertain events, such as games, matches, races, and other occurrences. The uncertainty of outcomes generates expectations and tension for gamblers. nawati, Prakoso, and Prihatmi (2015) assert that the development of information and communication technology significantly influences the gambling model and its payment methods. Unlike traditional gambling, which requires face-to-face interactions, physical means, and cash payments, online gambling leverages the internet, enabling games without physical encounters. The rapid evolution of online gambling in recent decades has facilitated easy access to various forms of gambling through the internet. Despite gambling's historical existence, online gambling possesses distinct characteristics that entail specific risks. This journal aims to identify and explore the diverse negative impacts associated with online gambling, while also delving into control measures that can be implemented to address these issues. Employing the qualitative descriptive phenomenology research method, our study will uncover shared meanings of the online gambling phenomenon as experienced by a group of students (Sahputra et al., 2022). The methodology employed here is the literature review method, wherein an independent activity is conducted to collect literature data, engage in reading and note-taking, and process research materials from various sources, such as books, online media, print media, and national and international journals. Online gambling has emerged as a concerning phenomenon globally. This journal examines various aspects related to the hazards of online gambling, encompassing social, economic, and health impacts. Additionally, we discuss control efforts that can be implemented to address these issues, with the ultimate goal of enhancing understanding and promoting more effective actions in addressing this problem. Online gambling presents numerous dangers that can adversely affect individuals and society at large. To tackle this issue, control efforts, including stringent regulations, public education, and rehabilitation programs, are imperative. A comprehensive understanding of the perils of online gambling will enable collaborative efforts to create a safer and healthier environment for everyone. Concrete actions are necessary to shield society from the detrimental impacts of online gambling.